2023
DOI: 10.1186/s12889-023-15015-0
|View full text |Cite
|
Sign up to set email alerts
|

Geographical variations and district-level factors associated with COVID-19 mortality in Indonesia: a nationwide ecological study

Abstract: Background Ensuring health equity, especially for vulnerable populations in less developed settings with poor health system is essential for the current and future global health threats. This study examined geographical variations of COVID-19 mortality and its association with population health characteristics, health care capacity in responding pandemic, and socio-economic characteristics across 514 districts in Indonesia. Methods This nationwide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 44 publications
0
3
1
Order By: Relevance
“…The observed different risks of COVID-19-related mortality and hospitalisation could be due to several factors such as different prevalence of older and comorbid population, as well as different level of health care capacity across the provinces. Although our study found an absence of association between number of health care workers at province-level with COVID-19-related mortality and hospitalisation, a previous nationwide ecological study in Indonesia, suggested that COVID-19 has disproportionately affected district with high proportion of elder population, high prevalence of diabetes mellitus, lower doctor to population ratio, higher life expectancy at birth, and lower level of formal education [37]. Other health care factors such as quality of COVID-19 diagnosis and case management may also affect the COVID-19 heterogeneity, but these factors were not evaluated in the current study.…”
Section: Plos Onecontrasting
confidence: 95%
“…The observed different risks of COVID-19-related mortality and hospitalisation could be due to several factors such as different prevalence of older and comorbid population, as well as different level of health care capacity across the provinces. Although our study found an absence of association between number of health care workers at province-level with COVID-19-related mortality and hospitalisation, a previous nationwide ecological study in Indonesia, suggested that COVID-19 has disproportionately affected district with high proportion of elder population, high prevalence of diabetes mellitus, lower doctor to population ratio, higher life expectancy at birth, and lower level of formal education [37]. Other health care factors such as quality of COVID-19 diagnosis and case management may also affect the COVID-19 heterogeneity, but these factors were not evaluated in the current study.…”
Section: Plos Onecontrasting
confidence: 95%
“…The mortality rate of COVID-19 in Indonesia displayed significant diversity, influenced by factors like varying incidence rates, different levels of pre-existing health conditions, the capacity of the healthcare system to respond to the pandemic, and the socioeconomic makeup of the population. The majority of COVID-19 cases and deaths were concentrated on Java Island, which is more developed and home to 152 million people, making up 56% of Indonesia's total population [8]. Recent studies conducted in Jakarta, the capital city of Indonesia, indicated that the virus had a disproportionate impact on older individuals with existing chronic health issues.…”
Section: Introductionmentioning
confidence: 99%
“…As of the end of 2022, a total of 6.6 million deaths out of 50 million COVID-19 cases have been reported worldwide [ 2 ]. In Indonesia, the overall incidence of COVID-19 was 2,050 per 100,000 populations, with a mortality rate of 55 per 100,000 populations [ 3 ].…”
Section: Introductionmentioning
confidence: 99%